Unresolved and misdiagnosed of floating sensation in young man - Zuraida Zainun; Muhammad Munzir Zuber Ahmadi (International Journal of Brain Sciences, 2024)
Persistent Postural-Perceptual Dizziness (PPPD) stands out as a prevalent peripheral vestibular disorder, earning its recognition in the International Classification of Vestibular Disorders in 2017. Characterized by chronicity, this condition manifests symptoms persisting for more than three months, encompassing a disconcerting array such as a floating sensation, unsteadiness, and dizziness. Notably, individuals afflicted with PPPD often report symptom exacerbation following prolonged standing, self-initiated motion, or exposure to dynamic visual stimuli. This case study spotlights a 22-year-old Chinese man who presented with a three-month history of a persistent floating sensation coupled with a six-month struggle against imbalance. Despite seeking medical attention in multiple healthcare centres, his condition failed to ameliorate. An initial Magnetic resonance imaging (MRI) scan of the brain returned normal results, perplexing healthcare providers about the etiology of his symptoms. The patient's ultimate diagnosis of PPPD sheds light on the complexity of vestibular disorders. PPPD can manifest in isolation or coexist with other conditions, confounding both patients and clinicians alike. The precise pathophysiologic mechanisms triggering PPPD remain elusive, underscoring the intricate nature of the disorder. In a positive turn of events, the case took a favorable trajectory with the implementation of balance rehabilitation. After undergoing three sessions of targeted intervention, the patient experienced a remarkable 70% improvement in his condition. This underscores the importance of tailored therapeutic approaches for PPPD, potentially offering a ray of hope for those grappling with its debilitating symptoms. This case not only highlights the clinical nuances associated with PPPD but also emphasizes the importance of a multidisciplinary approach in managing such conditions. As our understanding of vestibular disorders evolves, personalized and effective interventions, as exemplified in this case, become pivotal in enhancing the quality of life for individuals navigating the challenges posed by PPPD.
Keywords: Balance rehabilitation; PPPD; Pathophysiologic mechanisms; Therapeutic approaches; Vestibular Disorders